Childhood neuroendocrine tumours: a descriptive study revealing clues for genetic predisposition - Diets, I J (Br J Cancer, 2017)
BACKGROUND: Neuroendocrine tumours (NETs) are rare in children and limited data are available. We aimed to specify tumour and patient characteristics and to investigate the role of genetic predisposition in the aetiology of paediatric NETs. METHODS: Using the Dutch Pathology Registry PALGA, we collected patient- and tumour data of paediatric NETs in the Netherlands between 1991 and 2013 (N=483). RESULTS: The incidence of paediatric NETs in the Netherlands is 5.40 per one million per year. The majority of NETs were appendiceal tumours (N=441;91.3%). Additional surgery in appendiceal NETs was indicated in 89 patients, but performed in only 27 of these patients. Four out of five patients with pancreatic NETs were diagnosed with Von Hippel–Lindau disease (N=2) and Multiple Endocrine Neoplasia type 1 (N=2). In one patient with an appendiceal NET Familial Adenomatous Polyposis was diagnosed. On the basis of second primary tumours or other additional diagnoses, involvement of genetic predisposition was suggestive in several others. CONCLUSIONS: We identified a significant number of patients with a confirmed or suspected tumour predisposition syndrome and show that paediatric pancreatic NETs in particular are associated with genetic syndromes. In addition, we conclude that treatment guidelines for appendiceal paediatric NETs need revision and improved implementation.